Implementation of Digitalization in Budget Management Services Using Smart Finance - Purbaningtyas, Rani; Wiryawan, I Gede; Oktaviani, Siska Aprilia; Albaab, Mochammad Rifki Ulil (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
Budget management plays a crucial role in every type of organization. Effective budget management enables an organization to plan and allocate available resources efficiently. It also serves as a performance measurement tool for the organization. Inefficient budget management can lead to resource wastage. The implementation of the Smart Finance application, developed using a web platform, provides a digital solution for budgeting management services. This Smart Finance application has been tailored to meet the needs of user partners. Adjustments to the Smart Finance application are based on the identification and data collection of partner needs from the previous stages. The implementation of the Smart Finance application has also undergone testing and technical guidance support for users at all levels, ensuring that users find it easier to utilize the Smart Finance application.